Correction to: Impact of age at onset and newborn screening on outcome in organic acidurias. Issue 4 (12th December 2017) - Heringer, Jana; Valayannopoulos, Vassili; Lund, Allan M.; Wijburg, Frits A.; Freisinger, Peter; Barić, Ivo; Baumgartner, Matthias R.; Burgard, Peter; Burlina, Alberto B.; Chapman, Kimberly A.; i Saladelafont, Elisenda Cortès; Karall, Daniela; et al.
Abstract: Due to an unfortunate error during the typesetting process, the collaborators were presented incorrectly.